Chess for children, step by step : a new, easy way to learn the game - Lombardy, William; Marshall, Bette; Schnell, John. (Boston : Little, Brown, 1977)
Simple games teach beginning players how to move each chess piece and what each can do in a game.
Includes index.
Keywords: Chess for children; Chess